Needs a little TLC: examining college students' emergency remote teaching and learning experiences during COVID-19. Issue 7 (9th August 2021) - Shin, Minsun; Hickey, Kasey
ABSTRACT: The recent novel coronavirus (COVID-19) crisis has affected humanity and education worldwide as continued learning amidst massive school closures required the unprecedented decision to make a rapid transition from in-person learning to remote online learning. This abrupt and temporary shift to remote online learning due to crisis circumstances was described as emergency remote teaching (ERT). Using a multi-method approach, this study aimed to explore college students' emergency remote teaching experiences during the COVID-19 crisis. Analysis of online survey data revealed the various detrimental effects of the recent outbreak of COVID-19 and emergency remote teaching on the participants' educational and personal experiences. The results revealed not only that the participants have experienced learning loss and lack of motivation, but also that the pre-existing educational and social inequities seemed exacerbated and amplified during ERT and the COVID-19 crisis. Issues in terms of accessibility, digital divide, inequity, and mental/emotional/physical health that the participants, more likely females, experienced during emergency remote learning were especially concerning. The results highlighted the importance of addressing and combating the inequities, creating and maintaining a sense of community, and most significantly providing socio-emotional support, 'TLC' (Tender Loving Care; TLC (Tender Loving Care) is an expression, describing extra attention to make someone or something look or feel better), and compassion, to college students and the instructors during the uncertain times and as we move forward.